2016
DOI: 10.1002/cjoc.201500806
|View full text |Cite
|
Sign up to set email alerts
|

Design and Fabrication of Plasmonic Nanostructures with DNA for Surface‐Enhanced Raman Spectroscopy Applications

Abstract: Plasmonic nanostructures display unique and strongly enhanced optical properties, therefore hold great promise for a wide range of spectroscopic applications, particularly surface-enhanced Raman spectroscopy (SERS). It is well acknowledged that the major contributions to SERS arise from molecules positioned in nanojunctions where the optical field is intensively concentrated due to localized surface plasmon excitations. One of the key challenges in SERS therefore lies in the design and fabrication of plasmonic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 70 publications
0
1
0
Order By: Relevance
“…The results demonstrated that chitosan functionalized on the surface of GO showed low cytotoxicity greatly and improved biocompatibility. Surface functionalization of GO with macromolecules has been reported to remarkably attenuate its cytotoxic effects [ 45 ]. Hu et al reported that fetal bovine serum in cell medium markedly decreased the cell cytotoxicity of GO in non-small cell lung cancer A549 cells [ 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…The results demonstrated that chitosan functionalized on the surface of GO showed low cytotoxicity greatly and improved biocompatibility. Surface functionalization of GO with macromolecules has been reported to remarkably attenuate its cytotoxic effects [ 45 ]. Hu et al reported that fetal bovine serum in cell medium markedly decreased the cell cytotoxicity of GO in non-small cell lung cancer A549 cells [ 46 ].…”
Section: Resultsmentioning
confidence: 99%